Embriopatía por isotretinoína con microtia-anotia y cardiopatía. Presentación de un caso (2012)
Isotretinoin is a retinoid that derivates from vitamin A. It is indicated for recalcitrant nodular acne treatment, but it has been classified as teratogenic. A wide spectrum of birth defects including craniofacial, heart and nervous system malformations have been described associated to prenatal exposure to this drug. We report the case of a newborn with a history of prenatal exposure to isotretinoin with craniofacial defects, including facial paralysis, right anotia, left microtia and complex heart disease.